Cell free supernatants of Bifidobacterium adolescentis and Bifidobacterium longum suppress the tumor growth in colorectal cancer organoid model - Min Jung Kim; Myoung-Hyun Song; Yo-Sep Ji; Ji Won Park; Young-Kyoung Shin; Soon-Chan Kim; Gihyeon Kim; Beomki Cho; Hansoo Park; Ja-Lok Ku; Seung-Yong Jeong (Scientific Reports)
Abstract The probiotic gut microbiome and its metabolites are pivotal in regulating host metabolism, inflammation, and immunity. Host genetics, colonization at birth, the host lifestyle, and exposure to diseases and drugs determine microbial composition. Dysbiosis and disruption of homeostasis in the beneficial microbiome have been reported to be involved in the tumorigenesis and progression of colorectal cancer (CRC). However, the influence of bacteria-secreted metabolites on CRC growth is yet to be fully elucidated. In this study, we compared the microbial composition of CRC patients to healthy controls to identify distinct patterns of microbiota-derived metabolites in CRC patients. Metagenomic analysis demonstrated that beneficial bacteria strains; Blautia producta, Bifidobacterium adolescentis, and Bifidobacterium longum decreased, while Parabacteroides distasonis and Bacteroides ovatus were more prevalent in the CRC patient group. Treatment of cancer organoid lines with microbial culture supernatants from Blautia producta, Bifidobacterium adolescentis, and Bifidobacterium longum showed remarkable inhibition of cancer growth. This study demonstrates that the bacterial metabolites depleted in CRC patients may inhibit cancer growth and highlights the effects of microbiome-derived metabolites on CRC growth.